Serum copper in rural women taking combined oral contraceptive - Akhter, S; Shamsuzzaman, AK; Banarjee, M; Seema, SA; Deb, K (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):25-9 The abstract of this article is available on the PubMed website